Illustrated Postcard: Travel Figure, Dialogue, Info, Story, Advertisement - Malvinni, Paolo Domenico (E|C, 2022)
The study examines a series of picture postcards made for and sent from Riva del Garda between 1885 and the first years of the 20th Century. A medium that until a few years ago was employed side by side with other means of communication for promoting tourism and locales, relying on the pleasure that travelers and tourists derive from sending a message marking their presence in a certain place. The first picture postcards bear lithographic images on one side, more recent and more numerous ones have photos instead, images obtained by means of a physical connection, with an iconic value "strongly laden with inferences". The analysis addresses the strategies of the various authorial figures who produce such a traveling picture postcard, investigating the relationships that run between them. The first authorial function consists in the design and production, the second function envisions a postal customer choosing and addressing the postcard, having added a personal message. Looking at this series of cards one observes the selection of some (and not other) parts of the area and the town, noting the emphasis on useful details that offer and idea of the places' amenities and a certain possibility for using its spaces, modifying the pictures through decorations, inserts and visual tricks. We are dealing with texts that, once sent, are destined to produce interpretive readings for promotional effect, readings that constrain the sense of the piace represented by not including its complexity.